Automatic Controlling System of Drip Irrigation Based on GSM - , Alaa Rahhoom Hadi (Archives of Current Research International, 2017)
Due to the population increase over the world, every field and every of a department of life are updating themselves to increase the efficiency and output product. So the development of agriculture and agriculture-related sections must also be developed. Lack of rain and ultimately a lack of water scarcity is being observed in many areas of the world. The other side aspect is that there are a numerous number of leakages in the line, which waste much water. There is a need for automation, which is the ultimate solution of the problems. This paper emphasizes on this issue and resolves the issues and gives the valuable practical solutions. Automated techniques are the best solution for minimizing the power, reduce waste of water and increase the efficiency. To obtain the optimal method to irrigate crops, the Automated irrigation system is developed. The system contain to a temperature sensor, humidity sensor and soil moisture sensor, which is put in the root region of the plants. The significance of this paper includes the propose an efficient method in the field of irrigation systems by automatically monitor and control system. We suggested an innovative GPRS (general packet radio service). Which controlled embedded system for irrigation. the automatically system dependent on some parameters such as temperature, humidity and the water level in the soil by reading from the sensors and can automatically irrigate in the field without the involvement of farmer. Information is exchanged between far end and designed system via GPRS module.